2003
DOI: 10.1080/08037050310001084
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Urolithiasis, Blood Pressure and Salt Intake

Abstract: Objectives: To determine whether stone-formers have higher BP than controls drawn from the general population and matched for age, sex and ethnic origin and to compare the relationship between sodium and calcium excretion in the two groups. Patients and methods: Thirty-six patients [mean (AEstandard deviation, SD) = 49.0 AE 11.7 years; range 27-70 years] with kidney or ureteric stones and 108 controls (mean age of 49.6 AE 6.8 years; range 39-61 years), matched for gender, ethnic origin and age group were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…As a control, in parallel, cell lines stably expressing the empty vector pcDNA3.1(ϩ), were generated by the identical procedure. Paracellular 45 Ca 2ϩ flux studies of these cell lines were completed in identical fashion to those of wild-type OK cells as detailed above. For studies performed in the absence of sodium, both the apical and basolateral buffers consisted of 10 mM HEPES, pH 7.4, 140 mM KCl, 1 mM MgCl 2, 1 mM CaCl2, and 10 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a control, in parallel, cell lines stably expressing the empty vector pcDNA3.1(ϩ), were generated by the identical procedure. Paracellular 45 Ca 2ϩ flux studies of these cell lines were completed in identical fashion to those of wild-type OK cells as detailed above. For studies performed in the absence of sodium, both the apical and basolateral buffers consisted of 10 mM HEPES, pH 7.4, 140 mM KCl, 1 mM MgCl 2, 1 mM CaCl2, and 10 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo 45 Ca 2ϩ absorption assay. Intestinal Ca 2ϩ absorption from wild-type and NHE3 Ϫ/Ϫ mice was determined by measuring serum 45 Ca 2ϩ levels at time intervals post-oral gavage of a 45 Ca 2ϩ -containing solution essentially as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, metabolic acidosis induced hypercalciuria and hypocitraturia hastens nucleation and aggregation of CaOx crystals, potentiating the risk of calcium stone formation [29,30]. With respect to phosphate, it has been reported that increased urinary phosphate excretion couple with hyperoxaluria favors CaOx stone formation as CaP crystals act as nuclei for subsequent deposition of CaOx crystals [31].…”
Section: Discussionmentioning
confidence: 99%